Percepção de estudantes de enfermagem sobre o ensino da atenção à saúde de pessoas LGBTQIA+ - Araújo, Willian Martins (Universidade Federal de São Carlos, 2023)
Objective: to analyze nursing students' perceptions about their professional training for health care of LGBTQIA+ people. Methods: qualitative study, conducted with 19 nursing students through semi-structured interviews. Data were processed and worked through lexical analysis using IRaMuTeQ® software. Results: the textual corpus gave rise to two categories: professional nursing training on health of LGBTQIA+ people (subdivided into: curricular spaces addressing health of LGBTQIA+ people and Formative deficits for health care of LGBTQIA+ people) and Extracurricular spaces of professional training on health of LGBTQIA+ people (subdivided into: informal and extracurricular learning on health of LGBTQIA+ people and Work context and autonomy in learning about LGBTQIA+ health). Conclusion: addressing the health of LGBTQIA+ people in the training of nurses needs to expand beyond specific classes, which demands the creation of spaces within the curricular matrices that address the specificities required by this population, without, however, relegating them to extracurricular activities. Contributions to practice: problematization of the training of nurses for the health care of LGBTQIA+ people.
Nursing students' perceptions of teaching health care to LGBTQIA+ people
Keywords: Enfermagem; Estudantes de enfermagem; Ensino; Minorias sexuais e de gênero; Nursing; Students nursing; Teaching; Sexual and gender minorities; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA